KOMPARASI UNSUR FENG SHUI ALIRAN BENTUK DAN ILMU DESAIN INTERIOR PADA RESTORAN DAPUR BABAH ELITE DI JAKARTA - Sari, Sriti Mayang (Institute of Research and Community Outreach - Petra Christian University, 2009)
Feng shui is a form flow applied through experience and intuition for solving problems in interior design. Its application is often in opposition with the scientific study of interior design. The purpose of this research is to compare the form flow of Feng shui and the Interior Design theory. The results show that the two disciplines have different orientations in their methods of interior design. Feng shui is focused on the flow of qi energy whereas the scientific study of interior design is focused on fulfilling the comfort of the user. Although the two disciplines have different orientations, both have a similar purpose, which is to attract customers. Feng shui attempts to attract customers through presenting a good interior of a restaurant that is according to the Feng shui concept (colours that support qi energy) whereas the Interior Design discipline attracts customers by presenting an experience of an interesting atmosphere.